There’s More Than One Way to Tie a Ḥijāb: Female Conversion to Islam in Ukraine - Shestopalets, Denys (Islam and Christian-Muslim relations, 2021)
This article offers an analysis of female conversion to Islam in Ukraine as a complex and multifaceted phenomenon that involves a range of social, psychological and cultural factors. Based on 21 cases derived from media reports and face-to-face interviews, this study explores the primary reasons for conversion expressed by Ukrainian women, their experiences of wearing ḥijāb in public places and their perspectives on Christianity as their former religious tradition. Using Lofland and Skonovd’s theoretical perspective, the article demonstrates that the intellectual motif of conversion – on its own or sometimes in combination with other elements – may be the predominant one among Ukrainian female converts. Although for some women marriage still appears to be a significant factor in turning to Islam as a religious option, even in marriage-related cases converts often experience intense personal transformations tantamount to religious conversion.